COVID-19-Related Psychological and Psychosocial Distress Among Parents and Youth With Physical Illness: A Longitudinal Study - Ferro, Mark A.; Meyer, Samantha B.; Yessis, Jennifer; Reaume, Shannon V.; Lipman, Ellen; Gorter, Jan Willem (Frontiers in Psychiatry, 2021)
Despite the initial thrust of research aimed at understanding the impact of the COVID-19 pandemic on youth with physical illness and their parents, knowledge gaps in the literature remain, providing the impetus for additional investigation. This study described changes in psychological distress from prior to during the COVID-19 pandemic for parents and youth with physical illness, compared parent-proxy and youth self-reported perceptions of COVID-19-related psychosocial health, and modelled factors associated with psychological and psychosocial distress. There were 147 parent-youth dyads (2-16 years) from MY LIFE—a longitudinal study of youth with physical illness. The Kessler-6 (K6) measured psychological distress for the time before the COVID-19 lockdown (Dec19-Mar20) and during the pandemic (Dec20-Mar21) among parents and youth. COVID-19-related psychosocial health was measured using the CRISIS. Parents and youth reported increases in K6 scores (d=0.62 and 0.38). Parent-proxy reports on the K6 were lower versus youth self-reports prior to and during the pandemic (d=0.63 for both). In contrast, parents reported lower proxy CRISIS scores for worries (d=0.38) and effects of social restrictions (d=0.52). Pandemic parent K6 scores were associated with age, combined in-person and online schooling for youth, COVID-19-related worries, and effects of social restrictions. For youth, only COVID-19-related worries and effects of social restrictions were associated with K6 scores. Parent worries were associated with youth sex, parental stress, family functioning, online and combination learning, and social restrictions. Parental depression and worries were associated with effects of social restrictions. Youth worries were associated with online and combination learning and social restrictions. Youth disability, online learning, and worries were associated with effects of social restrictions. Few clinical factors are associated with COVID-19-related psychological and psychosocial distress. Instead, parent/family factors and youth learning environment have prominent roles in predicting outcomes and have implications for the health, education, and social services systems.